GEOLOGICAL, GEOCHEMICAL, AND MICROBIAL PROCESSES AT THE HYDRATE-BEARING HåKON MOSBY MUD VOLCANO: A REVIEW - Milkov A.V.; Vogt P.R.; Crane K.; Lein A.Yu.; Sassen R.; Cherkashev G.A. (My University, 2004)
Submarine mud volcanoes are point sources of fluid expulsion and oases of active geological, geochemical, and microbial processes in the deep ocean. The results of multidisciplinary investigations at the Håkon Mosby mud volcano (HMMV) in the Norwegian Sea at ∼1250 m water depth are reviewed in this paper. Seafloor morphology, lithotypes, geochemical, and biological processes at the HMMV are concentrically zoned. The zonation is controlled by ejection of sediment, water, and gases (mainly methane) accompanied by high heat flow in the mud volcano crater. A structural gas hydrate accumulation is associated with the HMMV. Gas hydrate is abundant only in a relatively narrow zone where optimal conditions (low temperature and high gas concentration) exist for gas hydrate crystallization. Authigenic minerals, bacterial mats, and chemosynthetic communities typical of cold seep environments are present. Rapid anaerobic sulfate-dependant oxidation of methane is thought to be mediated by a consortium of methanogens and sulfate-reducing bacteria. Although methane is oxidized in sediments at high rates, a significant portion of this gas may escape into the ocean, mainly as diffuse flux. In the water column, methane is rapidly dissolved and oxidized. This observation supports the hypothesis that gas flux from deep-water mud volcanoes contributes to the oceanic carbon pool, but not to the atmosphere. The HMMV represents an important natural laboratory and provides insight to processes at the interface of methane-rich sediments and cold bottom water in the deep ocean. Future studies may best focus on accurate direct measurements of gas flux and quantification of the biogeochemical cycling of major chemical elements in shallow sediment.
Keywords: Mud volcano; Methane; Gas flux; Carbon cycle; Anaerobic methane oxidation; Gas hydrate